Technique of Endoscopic Biopsy of Islet Allografts Transplanted into the Gastric Submucosal Space in Pigs. Issue 12 (December 2013) - Fujita, Minoru; McGrath, Kevin M.; Bottino, Rita; Dons, Eefje M.; Long, Cassandra; Kumar, Goutham; Ekser, Burcin; Echeverri, Gabriel J.; Hata, ‡‡, Jiro; Haruma, Ken; Cooper, David K. C.; Hara, Hidetaka
Currently, islet cells are transplanted into the liver via portal vein infusion. One disadvantage of this approach is that it is not possible to adequately biopsy the islets in the liver to assess for rejection. Islet transplantation (Tx) into the gastric submucosal space (GSMS) can be performed endoscopically and has the potential advantage of histological evaluation by endoscopic biopsy. The aim of this study was to determine whether a representative allograft sample could be obtained endoscopically. We performed islet Tx into the GSMS in nonimmunosup-pressed pigs using simple endoscopic submucosal injection. Islets were transplanted at four sites. Endoscopic ultrasonography and biopsy of the transplanted islets at two sites by modified endoscopic submucosal dissection were carried out successfully in all pigs 5 days after islet Tx. Tissue obtained at both biopsy and necropsy (including full-thickness sections of the gastric wall around the sites of the remaining islets and biopsies) were examined by histology and immunohistochemistry to confirm the presence of the islet grafts and any features of rejection. Representative allograft sampling was successfully obtained from all biopsy sites. All biopsies included islets with insulin-positive staining. There was significant CD3 + and CD68 + cell infiltration in the islet masses obtained at biopsy and from sections taken at necropsy, with similar histopathological features. Endoscopic biopsy of islet allografts in the GSMS is feasible, provides accurate histopathological data, and would provide a significant advance if translated into clinical practice.